2014
DOI: 10.1016/j.jobcr.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A technique for using short term soft liners as complete dentures final impression material

Abstract: Soft liner Impression materialResorbed ridges a b s t r a c t Tissue conditioners can be used to condition abused tissues, record functional impressions, make temporary relining for surgical splints and obturators, and for other clinical applications, mainly because of their specific viscoelasticity. Their function in complete denture fabrication is debatable but their use as a functional impression material has been proved. The present article describes a technique for using tissue conditioners as functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…[13][14][15] It has been shown that over a period of 1 week, water sorption increased from 0.2 to 5.6 mg/cm, and solubility ranged from 0.03 to 0.40 mg/cm for various commercial products. [16][17][18] One of the main problems with silicone-based TCs concerns bonding to the denture base surface. It has been shown that "adhesion" between the lining mate-rial and base of the denture is the most common source of failure of a resilient-lined denture.…”
Section: Physical Properties Of Tcsmentioning
confidence: 99%
“…[13][14][15] It has been shown that over a period of 1 week, water sorption increased from 0.2 to 5.6 mg/cm, and solubility ranged from 0.03 to 0.40 mg/cm for various commercial products. [16][17][18] One of the main problems with silicone-based TCs concerns bonding to the denture base surface. It has been shown that "adhesion" between the lining mate-rial and base of the denture is the most common source of failure of a resilient-lined denture.…”
Section: Physical Properties Of Tcsmentioning
confidence: 99%
“…1 [14,18,19]. Soft tissue liners are considered as an economical method to the patient, additionally it helps in increasing the stability and retention of a denture [20].…”
Section: The Potential Therapeutic Uses Of Soft Tissue Liners In Dent...mentioning
confidence: 99%
“…Протезы, изготовленные при недостаточном учёте морфологических особенностей тканей протезного ложа, способствуют усилению атрофических процессов альвеолярных гребней особенно на фоне малоподатливой слизистой оболочки [1,8,14,16,19]. Особенно неблагоприятными клиническими условиями протезирования отмечаются при прогнатическом и прогеническом соотношении альвеолярных отростков фронтальных сегментов челюстей [12,17] в сочетании вариантов диспропорций альвеолярных отростков жевательных и фронтальных сегментов челюстей [9,18].…”
Section: литературный обзорunclassified